Destin des identifications dans la perte : le fantôme - Ophélie Méchin (Conserveries Mémorielles)
Through practice centered on bereavement, clinicians have observed phenomenon of « revenance » that, at times, take the shape of hauntings. These ghosts are commonly considered as interruptions of the grieving process. If mourning necessarily involves pain and suffering, does the appearance of ghosts always impede on the grieving process ? Are these apparitions always pathological or are they, though frightening at times, the building blocks of this process ? Moreover, what about those apparitions that do not provoke a sense of uneasiness ? Following Freud's work on grief, Fedida and then Laufer have provided useful insight on this phenomenon of « revenance ». The mourning person must create a mental place of burial : the ghost is the sign that his mental life is anew after the devastation of trauma and loss. The appearance of these ghosts, as uncomfortable and anxiety-provoking as it may be, signal the possibility and start of the grieving process. But clinical work with our elders suggests that these ghosts are related to the subject’s identities. As an ancient object of identification, the ghosts redefines the contours of the subject’s identity and reveals its role of maintaining and preserving a sense of self, a self composed of a multitude of relationships and identifications with others.